Resilience Capabilities of Female Inmates who are Covid-19 Survivors in the Pekanbaru Women's Correctional Institution - Padmono Wibowo; Ghaneisya Anggareksi; Mulyani Rahayu; Maki Zaenudin Subarkah (Jurnal Ilmiah Kebijakan Hukum, 2022)
Resilience is an individual's ability to adapt positively, be able to survive and remain stable and healthy when facing unpleasant and risky conditions, such as Covid-19 pandemic. This study is to describe the resilience ability of female inmates who are Covid-19 survivors at the Pekanbaru Women's Correctional Institution. In addition, this study aims to determine the sources of resilience in female prisoners who survived Covid-19 at the Pekanbaru Women's Correctional Institution to improve the resilience capabilities of prisoners. The research methods used are qualitative approach and descriptive design. Based on the results of the study, it is known that the sources of prisoners' resilience abilities in dealing with Covid-19 originating from self perception is positive thinking, acceptance, self-motivation, others' supports, being diligent in worship and visitation, while those from self efficacy are self-control, looking for solutions, willing to repent, adapting, being independent, being grateful, appreciating time, interpreting life, doing good, and being devoted, while what comes from I Have are the support and the rules. The results of the study also found that there were female prisoners who survived Covid-19 who were Non-Resilient are paranoia, stress, low self-esteem and denials, self-isolation, indifference, fear and pressure,  breaking the rules and lack of attention. Therefore, intense efforts need to be made so that non-resilient prisoners have the ability to be resilient in dealing with Covid-19.